Employee retention at schools in challenging contexts – can transformational leadership alleviate intentions to resign? - Windlinger, Regula; Warwas, Julia; Hostettler, Ueli (Swiss Journal of Educational Research, 2023)
Working at schools in challenging contexts is characterised by pedagogical challenges that can lead to an intention to resign on the part of teachers. The article examines the relationship between the socio-spatial context of the school and turnover intentions among 1,658 teachers from 114 schools in the canton of Berne and analyses the role of transformational leadership by the school management. Results show that challenging circumstances of pedagogical work are positively, and transformational leadership negatively associated with intentions to resign, but the effects occur independently of each other. This suggests that transformational leadership contributes to staff retention but does not necessarily compensate for adverse working conditions.